CORRELATION BETWEEN PROLONGED STANDING AND PLANTAR FASCIITIS - Ni Ketut Maya Purvitagiri; Linda Dewanti; Sulis Bayusentono; Indrayuni Lukitra Wardhani (Universitas Airlangga, 2017)
Background: Plantar fasciitis (PF) is the most common heel pain in adult. It is estimated that it affects as much as 10% of the population over the course of their lifetime. Previous study mention that prolonged standing is one of the risk factor of PF, however other study suggests that there is low evidence of prolonged standing may cause PF. The objective of this study was to findout whether or not prolonged standing may correlate to PF. Methods: This cross-sectional with total sampling study involved 73 workers in total. 35 of them did not fulfill the inclusion criteria, hence only 38 of subjects were used. The data collected using questionnare and analyzed using Chi-square. with p-value (p) <0.05 and confidence interval (CI) 95%. Results: There is no correlation between prolonged standing and PF symptoms p= 0.249. Conclusion: There is no correlation between prolonged standing and plantar fasciitis and even though in other study suggest that BMI, and age also the risk factor of PF this was not consistently confirmed in this study. Further research may use larger number of subjects and use other measure to determine the definition of prolonged standing.